2020
DOI: 10.1177/1471301220929543
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of family carer’s understandings of people with dementia’s expectations for the future

Abstract: Background There is little evidence that outlines how family carers understand the person with dementia’s perspective, values and anticipated future needs. Whilst people with dementia should be consulted about their own quality of life and care values, carers – otherwise known as care partners – require such understandings to ensure that the support the person receives into the future upholds their quality of life and is consistent with what they desire. Aim This research aimed to explore and describe family c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Therefore, providing interventions to support carers is needed to tackle these challenges, which requires an understanding of their expectations regarding dementia care (Davies et al, 2020; Kampanellou et al, 2019). Previous research has focused on the expectations of people with dementia (Read et al, 2017), carers’ understanding of their relative’s expectations (Read et al, 2021) and expectations regarding formal care (Kiljunen et al, 2018). It is reported that people with dementia are concerned about the loss of functional capacity and uncertainty about the future (Read et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, providing interventions to support carers is needed to tackle these challenges, which requires an understanding of their expectations regarding dementia care (Davies et al, 2020; Kampanellou et al, 2019). Previous research has focused on the expectations of people with dementia (Read et al, 2017), carers’ understanding of their relative’s expectations (Read et al, 2021) and expectations regarding formal care (Kiljunen et al, 2018). It is reported that people with dementia are concerned about the loss of functional capacity and uncertainty about the future (Read et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that people with dementia are concerned about the loss of functional capacity and uncertainty about the future (Read et al, 2017). To address issues that align with the diagnosis, carers help sustain their relative’s quality of life, independence and decision making (Read et al, 2021). However, there is a paucity of evidence into carers’ expectations of dementia care.…”
Section: Introductionmentioning
confidence: 99%
“…First, READyR assesses the care values of the person living with dementia, or what is most important to the person living with dementia. This information is critical to knowing the person living with dementia, and has been identified as an essential element of planning for future care ( Lord et al, 2020 ; Read et al, 2021 ). Practically speaking, knowing what is most important to the person living with dementia helps to focus the dementia care needs assessment on the areas most central to each individual’s well-being, rather than attempting to give equal attention to an extensive and often overwhelming inventory of potential care needs.…”
Section: Discussionmentioning
confidence: 99%